The effects of on-call duties on cognitive functions in anaesthesia residents husm - Ahmad , Azila (2010)
INTRODUCTION Cognitive functions play a vital role in safe anaesthetic practice and there are various factors that affect the cognitive functions. OBJECTIVES The aim of this study is to determine the effects on cognitive functions in anesthesia residents doing on-call duty in HUSM and to compare between demographic factors and on-call features with cognitive functions. METHODOLOGY This study includes all the anesthesia residents in the Department of Anaesthesiology, HUSM after written informed consent was obtained. The data was collected from 1st January until 28th February 2010. Four cognitive tests were used in this study which were Mini Mental State Examination (MMSE), Stroop Color Word Test (SCWT), Concentration Test (CT) and Reaction Time Test (RTT). Other associated factors affected by on-call such as Stanford Sleepiness Scale (SSS), Busy Score (BS) and psychological Stress Score (PSY) were also recorded.